2012
DOI: 10.1631/jzus.b1100310
|View full text |Cite
|
Sign up to set email alerts
|

Propolis modulates vitronectin, laminin, and heparan sulfate/heparin expression during experimental burn healing

Abstract: The beneficial effects of propolis on experimental wounds make it a potential apitherapeutic agent in topical burn management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Despite therapeutic activity of the drug, it should also quench radical activity. Therefore European propolis (including Polish origin epitherapeutic agent), a natural plant resin that is produced by honey bees, seems to be an optimal agent for the treatment of thermal injuries due to its antimicrobial, anti-inflammatory, antitumor, immunomodulatory, and last but not least antioxidant activity [710]. Beneficial biological effect of propolis has been widely used in dermatology for injuries healing, thermal damage and external ulcers therapy, healing time reduction, wound contraction increase, and tissue repair acceleration [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite therapeutic activity of the drug, it should also quench radical activity. Therefore European propolis (including Polish origin epitherapeutic agent), a natural plant resin that is produced by honey bees, seems to be an optimal agent for the treatment of thermal injuries due to its antimicrobial, anti-inflammatory, antitumor, immunomodulatory, and last but not least antioxidant activity [710]. Beneficial biological effect of propolis has been widely used in dermatology for injuries healing, thermal damage and external ulcers therapy, healing time reduction, wound contraction increase, and tissue repair acceleration [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrary to the last mentioned natural agent, silver sulphadiazine conventionally used for topical burn therapy, effective in controlling the infection of damaged skin, may lead to prolongation of the wound reepithelization process [10, 1416]. …”
Section: Introductionmentioning
confidence: 99%
“…The expression of HS/H constituting a small amount of wound matrix total GAGs [6] was precisely discussed in our previous work [17]. As can be seen from Figure 2(a) the total amount of GAGs increased in the wound bed treated with propolis, AgSD, NaCl, and propolis vehicle.…”
Section: Resultsmentioning
confidence: 83%
“…According to the results of our study, it can also be concluded that propolis skin ointment appears to have beneficial effects on healing venous ulcers. Propolis has been shown to stimulate various enzyme systems, cell metabolism, circulation, and collagen formation as well as improve the healing of burn wounds [14]. In the study published by Kurson [15], sixty-four patients with tibial skin ulcers, aged from 23 to 98 years old, were treated using propolis extract in an ointment form.…”
Section: Discussionmentioning
confidence: 99%